PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE PADA KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR - Saraswati, I Gusti Ayu Made Reina Ary; Damayanthi, I Gusti Ayu Eka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
A good company's financial performance is a positive signal for investors that is obtained from the company's efforts to generate profits. This study aims to examine the influence of Intellectual Capital and Good Corporate Governance on the financial performance of manufacturing companies listed on the IDX for the period 2017-2020. A sample of 33 companies was taken by purposive sampling from a total population of 155 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The test results with multiple linear regression analysis show that there is a significant positive effect between the variables of intellectual capital, managerial ownership, institutional ownership, and independent commissioners on financial performance.